2012
DOI: 10.1016/s0968-8080(12)39602-x
|View full text |Cite
|
Sign up to set email alerts
|

Unmet health needs identified by Haitian women as priorities for attention: a qualitative study

Abstract: This 2009 qualitative study investigated Haitian women’s most pressing health needs, barriers to meeting those needs and proposed solutions, and how they thought the community and outside organizations should be involved in addressing their needs. The impetus for the study was to get community input into the development of a Family Health Centre in Leogane, Haiti. Individual interviews and focus group discussions were conducted with 52 adult women in six communities surrounding Leogane. The most pressing healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 17 publications
(12 reference statements)
1
12
0
Order By: Relevance
“…Based on a review of published qualitative research on maternal health-seeking behavior in Haiti and our own academic training and professional experiences, we developed our question guide and study procedures (see Additional file 2: Question Guide for Focus Groups) [23–25]. The FGDs were held in a private room at our collaborating organizations’ clinics and were conducted in Haitian Creole, recorded, and lasted between sixty and ninety minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Based on a review of published qualitative research on maternal health-seeking behavior in Haiti and our own academic training and professional experiences, we developed our question guide and study procedures (see Additional file 2: Question Guide for Focus Groups) [23–25]. The FGDs were held in a private room at our collaborating organizations’ clinics and were conducted in Haitian Creole, recorded, and lasted between sixty and ninety minutes.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, reproductive health services were not provided for some women who could not leave their children or the elderly alone in the settlements. A number of studies reported that reproductive health services were not available and accessible for the affected people, including the groups with less mobility, such as widows, the elderly, and disabled people [ 9 , 11 , 41 , 42 ]. Developing an active monitoring system to follow the reproductive health status of all affected people in destroyed regions may increase the effectiveness and coverage of reproductive health services and improve people’s well-being after disasters.…”
Section: Discussionmentioning
confidence: 99%
“…Urrutia et al (2012) report that Haiti reflects this same trend. For example, pregnant women did not use traditional birth attendants (TBAs) or access facility-based health care services due to cost [12]. The 2008 and 2012 Demographic and Health Surveys (DHS) also underscore cost as a key factor in deterring women aged 15–49 years from consulting a health care provider when they are sick.…”
Section: Introductionmentioning
confidence: 99%
“…8Following the earthquake of 2010, international donor funding for the health sector jumped from covering 43% of current health expenditures in 2010 to covering 65% of current health expenditures in 2011 [12]. This additional significant increase in donor funding for the health sector was driven by the devastating earthquake in 2010 and emphasized disaster relief aid.…”
mentioning
confidence: 99%